UHPLC–MS/MS analysis of cocoa bean proteomes from four different genotypes. (15th January 2020) - Scollo, Emanuele; Neville, David C.A.; Oruna-Concha, M. Jose; Trotin, Martine; Cramer, Rainer
Highlights: 61 differentially abundant proteins (fold change of ≥2) among four cocoa genotypes. Majority of these 61 proteins are involved with metabolism and energy. Changes in protease abundances can be correlated with flavour profiles of genotypes. Genotype-specific levels of amino-oxidases and alcohol dehydrogenases were detected. PCA allows separation of genotypes and shows correlation between close genotypes. Abstract: In this study the proteomic profiles of cocoa beans from four genotypes with different flavour profiles were analysed by bottom-up label-free UHPLC–MS/MS. From a total of 430 identified proteins, 61 proteins were found significantly differentially expressed among the four cocoa genotypes analysed with a fold change of ≥2. PCA analysis allowed clear separation of the genotypes based on their proteomic profiles. Genotype-specific abundances were recorded for proteases involved in the degradation of storage proteins and release of flavour precursors. Different genotype-specific levels of other enzymes, which generate volatiles compounds that could potentially lead to flavour-inducing compounds, were also detected. Overall, this study shows that UHPLC-MS/MS data can differentiate cocoa bean varieties.